Influence of organoleptic properties of the feed and nursery diet complexity on preweaning and nursery performance - R C Sulabo; C D Risley; Michael D Tokach; Joel M DeRouchey; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2008)
Two experiments were performed to determine the effects of adding an enhanced feed flavor to the creep feed on the proportion of piglets consuming creep feed within litters and preweaning performance (Exp. 1) and the interactive effects of preweaning exposure to the flavor, nursery diet complexity, and flavor addition to nursery diets on postweaning performance (Exp. 2). In Exp. 1, 50 sows (PIC 1050) were blocked according to parity and date of farrowing and allotted to 2 experimental treatments in a randomized complete block design. Treatment 1 was a creep diet with no flavor (negative control), and treatment 2 was the negative control diet with the enhanced milky flavor (Luctarom) included at 1,500 ppm (3 lb/ton). Both creep diets contained 1.0% chromic oxide and were offered ad libitum from d 18 until weaning on d 21. In Exp. 2, 480 weanling pigs (PIC, 14.5 lb and 20 ± 2 d) from Exp. 1 were blocked by initial weight and allotted to 1 of 8 treatments in a randomized complete block design with preweaning exposure to the flavor (exposed vs. unexposed), nursery diet complexity (complex vs. simple), and flavor addition to the nursery diets (with vs. without flavor) as treatment factors. In Exp. 1, no differences in weaning weight (P>0.53), total gain (P>0.77), and ADG (P>0.77) were observed between litters or pigs fed creep with and without the flavor. Flavor added to the creep feed did not influence total (P>0.66) or daily (P>0.66) creep feed intake of litters or the proportion of creep feed eaters (P>0.41) in whole litters. In Exp. 2, a tendency for a 3-way interaction for ADG from d 5 to 10 (P<0.11), d 10 to 28 (P<0.09), and d 0 to 28 (P<0.06) was observed. Postweaning ADG of pigs exposed to the flavor in creep feed and pigs fed flavored complex diets was greater than that of pigs in any other treatment combination. Increasing diet complexity improved (P<0.01) ADG and ADFI during both phases. Adding flavor in the creep feed had no effect on F/G (P>0.34) and pig BW (P>0.45) in both periods post-weaning. Adding Luctarom to starter diets tended to improve ADFI (P<0.06) during d 0 to 5. In conclusion, adding Luctarom to the creep feed did not affect litter creep feed intake, proportion of piglets consuming creep feed, and preweaning performance when creep was provided for 3 d before weaning. Pre-weaning exposure to Luctarom improved postweaning daily gain of pigs fed complex diets supplemented with the same flavor but did not influence performance of pigs fed simple diets.; Swine Day, 2008, Kansas State University, Manhattan, KS, 2008
Keywords: Swine day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-074-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1001; Feed intake; Flavor; Piglet; Swine